Analisis Kelemahan Fitur Cloud pada Access Point Berbasis Cloud - Kaiva Alby Aufinanta (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
This study aims to identify and analyze vulnerabilities of Cloud features in Access Points through an experimental approach. Cloud features in Access Points include network resource management, storage, data processing, and internet-based device management services used to monitor device traffic, update firmware, and perform centralized configuration. The research began with the design of Access Point configurations, followed by a simulation of a Man-in-the-Middle (MITM) attack using the SSL Strip method. Testing was conducted using a Ruijie Reyee RG-EW1200 Access Point with the support of Bettercap software on the Kali Linux operating system and a Windows virtual machine. The research process involved identifying Cloud features of the device, collecting technical documentation, executing SSL Strip attack simulations, and analyzing discovered vulnerabilities. Experimental results revealed specific vulnerabilities in the Cloud security system of the Access Point, including data leakage of Password, SSID, IP, Serial Number, Network Name, Device Type, Firmware Version, MAC Address, Forward Mode, Access Point Status, and Port Status, which were then analyzed to provide mitigation recommendations. These findings are expected to serve as a reference for enhancing security of Cloud features in network devices, particularly centralized management-based Access Points.